"Impact of Soil Dynamics on Sustainable Architecture and Construction Practices in the Beas Valley, Kullu: A Study of Legal and Policy Frameworks" (International Journal of Food and Nutritional Sciences, 2022)
This study investigates the profound influence of soil dynamics on sustainable architecture and construction practices in the Beas Valley, Kullu. The region's unique geological characteristics, including mountainous terrain and diverse soil types, pose significant challenges and opportunities for architectural design and construction techniques. This research explores how soil properties such as bearing capacity, stability, and erosion susceptibility shape architectural decisions, material choices, and construction methodologies. Furthermore, it examines the critical role of legal and policy frameworks at national and state levels in regulating soil management, environmental conservation, and sustainable development practices in Himachal Pradesh. By analyzing case studies and current practices, this study aims to propose recommendations for enhancing sustainability in architectural and construction practices while preserving the ecological integrity and cultural heritage of the Beas Valley.